PROBLEMATIKA PENDIDIKAN ISLAM: TANTANGAN MASA KINI DAN MASA AKAN DATANG - Firman Sidik; Syarifuddin Ondeng; Saprin Saprin (LP2M IAIN Sultan Amai Gorontalo, 2023)
This article aims to look at the problems of Islamic education that occur in the present and in the future so that they can become a solution to improve Islamic education. The method used in this study is the library, where the data in this study were obtained from various relevant literature and then analyzed comprehensively. The results of the study found that the problems that exist in Islamic education today are paradigm problems, objective problems, material problems, method problems, evaluation problems. Meanwhile, the future challenges are a crisis of values, a crisis of concepts, a lack of idealism, pragmatism, and technology